Research on the Archaeoacoustic Simulation of Daxiong Main Halls in Chinese Buddhist Temples Through Comsol Tool - Tang Ziqing; Lu Fenghua (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
The acoustic analysis plays an irreplaceable role in obtaining information on Chinese Buddhist main halls tradition and relative practice that includes sound, deepening our comprehension of Chinese Buddhist architectural heritage. Various ceremonies and dojos constitute rich types of Buddhist main halls’ sound fields. In this paper, the indoor sound fields of four main halls in the Buddhist temples are researched and compared. This paper used Sketchup to build the models and simulate sound fields when conducting ceremonies and dojos using Comsol Multiphysics software. The four main halls are Chongshan temple main hall, Xiantong temple main hall, Shuxiang temple Manjusri hall and Bodhisattva Top main hall, which are located in separately four temples of Shanxi Wutai mountain in China. Targeting three acoustic parameters including the reverberation time(RT), the first ray arrival time(Re1first) and surface sound pressure level(SPL) distribution, we simulated the acoustic effect of the space occupancy, Buddha realm space and worship space, indicating that the acoustic wave diffusion rate was positively correlated with proportion of hall height to depth, while the first arrival time is exactly the opposite. The largest RT at 2000Hz(about 1.3s)in the shortest period for 500Hz voice was observed in the main hall of Pusa Peak, while T60 even reached 4s in Xiantong temple main hall. The acoustic wave transmission rate was positively correlated with proportion of hall’s height to depth, but the first ray arrival time was the opposite. The main hall of Pusa Peak had the shortest (0.0150s) first ray arrival time，the Shuxiang temple main hall had the longest time(0.0381s). In all the cases, appearing of the